Sains Berbasis Nilai: Kajian Aksiologis dan Etis - Putri, Bintang; Winarno, Agung; Subagyo Subagyo (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This article examines the role of axiology as a value dimension in the philosophy of science, which serves to guide science so that it not only produces knowledge but also provides benefits that align with humanitarian, ethical, and sustainable values. This research uses a library study method by reviewing various literature discussing the concept of axiology. The results of the study indicate that science cannot be viewed as a value-free activity, because every stage of the scientific process, from problem selection and method development to data interpretation and application of research results, is constantly influenced by social norms, moral considerations, and certain values. Therefore, axiology plays a crucial role in ensuring that scientific progress prioritizes human welfare and does not have destructive impacts. Furthermore, critical thinking skills are an important element in the application of axiology, as they enable humans to assess and consider the benefits and consequences of science more deeply. This study also emphasizes that scientists have a moral responsibility both internally, such as maintaining academic integrity and scientific objectivity, and externally, namely ensuring that research results are utilized for the common good. Thus, this article highlights the importance of integration between science, ethics, and values ​​as a foundation for developing knowledge that is not only scientifically correct, but also morally good and beneficial for the sustainability of life.